Enric Prat de la Riba: l’ideologia del pragmatismo nazionalista catalano (Spagna contemporanea. Rivista semestrale di storia, cultura, istituzioni, 1992)
Enric Prat de la Riba: the ideology of the Catalan nationalist pragmatism.This research started from the success of Enrico Prat de la Riba’s work and from the writings on the Catalan politician, but it does not claim to be exhaustive. Then it examines the cultural roots of Prat’s nationalism highlighting the influence of krausism, Prat’s conception of race, as well as his relationship with Eugeny d’Ors and Taine’s influence.